Microwave assisted extraction of total phenolic compound from pineapple peel and core: article - Abdul Halim, Syazwani; Md.Zaki, Nurul Asyikin (2017)
A microwave assisted extraction system was used to extract total phenolic compound (TPC) from pineapple peel and core. The effect of microwave power (180,300,450W) and extraction time (2 and 3min) were investigated. Pineapple peel and core were extracted with ethanol solvent. The highest extraction time for peel and core were 3min(180W) and 2min (300W). Meanwhile, the optimum microwave power obtain for both peel and core was 300W. The analysis was determined by using UV spectrophotometer at 760nm and the result was compared with standard curve of Gallic acid equivalent (mg/L). The results demonstrated that MAE could be a fast and reliable method for quantitative analysis of phenolic compounds in pineapple peel and core.